On Analysis of Cloth Drape Range Data - Jojic, Nebojsa; Huang, Thomas S. (1998)
In this paper we present an algorithm for analysis of the range data of cloth drapes. The goal of the analysis is estimation of parameters for modeling and the geometry of the underlying object. In an analysis-by-synthesis manner, the algorithm compares the drape of the model with the range data and searches for the best t. It can be applied to any physics-based cloth model. The motivating application is fashion design using CAD systems, but the ability of the algorithm to estimate the shape of the object supporting the scanned cloth indicates the possibility of utilizing cloth models to overcome problems in human tracking algorithms, caused by clothing.